2012
DOI: 10.2139/ssrn.2084708
|View full text |Cite
|
Sign up to set email alerts
|

Does Corporate Governance Affect Stock Liquidity in the Tunisian Stock Market?

Abstract: Abstract:The aim of the current paper is to study the link between the effects of corporate governance on information asymmetry problems and stock liquidity in the Tunisian Stock Market. We use a sample of 49 Tunisian firms listed between 1998 and 2007. Our results show that corporate governance has direct and indirect effects on stock liquidity. Threat of expropriation exerted by family and foreign shareholders discourages reluctant investors, which decreases stock liquidity. In contrast, they invest their ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 68 publications
3
15
0
Order By: Relevance
“…Corporate governance system (or structure) is set of mechanisms, relationships, rights and responsibilities that are put in place by members of a system for the effective and efficient functioning of the firm and the improvement of shareholders' value. Furthermore, it has been observed that companies with effective corporate governance structures (CGS) attract investors thereby leading to increase in companies' value and decrease in cost of equity (Loukil & Yousfi, 2010 Financial scandals around the world and the recent collapse of major corporate institutions in the USA had brought to the fore , once again, the need for the practice of good corporate governance, which is a system of managing the affairs of corporations with a view to increasing shareholder value and meeting the expectations of the other stakeholders".…”
Section: Corporate Governance Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corporate governance system (or structure) is set of mechanisms, relationships, rights and responsibilities that are put in place by members of a system for the effective and efficient functioning of the firm and the improvement of shareholders' value. Furthermore, it has been observed that companies with effective corporate governance structures (CGS) attract investors thereby leading to increase in companies' value and decrease in cost of equity (Loukil & Yousfi, 2010 Financial scandals around the world and the recent collapse of major corporate institutions in the USA had brought to the fore , once again, the need for the practice of good corporate governance, which is a system of managing the affairs of corporations with a view to increasing shareholder value and meeting the expectations of the other stakeholders".…”
Section: Corporate Governance Systemsmentioning
confidence: 99%
“…Thus, the long-term success and survival of organizations may be assured when entrepreneurial orientation becomes an organization-wide phenomenon. To this end, several scholars (e.g Dess and Lumpkin, 2005;Naldi, Nordqvist, Sjoberg& Wiklund, 2007) are of the opinion that firms which are highly entrepreneurial in their orientation achieve their goals and objectives efficiently. Aguilera, Filatotchev, Gospel, & Jackson (2008) submitted that Corporate Governance urges managers to be disciplined and committed to shareholders' wealth maximization.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been conducted on the issue. Foreign owners reduce CEO power (Ben Cheikh & Loukil, ) and decrease stock liquidity (Loukil & Yousfi, ). boldUFOR0.5embold=0.5em{left1if the utlimate owner is foreign investorleft0otherwise SIZE is the measure of the firm size assessed by the book value of assets. GROW is the annual growth rate of assets.…”
Section: Sample and Variablesmentioning
confidence: 99%
“…Despite the fact that more recent studies on emerging markets provide evidence that owner identity is more important than ownership structure (e.g., Dyck, 2001;Loukil & Yousfi, 2013;Omran, Bolbol, & Fatheldin, 2008;Wu, Xu, & Yuan, 2009), empirical studies (see among others Boubakri, Cosset, & Saffar, 2013) have paid little attention to the risk-taking behaviour of owners. From an agency perspective, women are considered independent directors and their appointment to the board may only be decided by the dominant shareholders.…”
Section: Corporate Governance Ownership Structure and Risk-takingmentioning
confidence: 99%
See 1 more Smart Citation